STRATEGY OF CULTURAL PRESERVATION AND CULTURAL CONSERVATION AT THE CULTURE OFFICE OF BONE REGENCY - Hasnawati Hasnawati; Mega Edarwati; Irmawati Irmawati; Asdar Asdar; Indrawati Indrawati (JURNAL ILMIAH EDUNOMIKA, 2023)
Cultural heritage plays a crucial role in human life, and efforts are needed to conserve it to preserve the essence and existence of culture. This study aims to formulate the research problem of preserving culture and cultural heritage at the Bone Regency cultural office and evaluating the strategy for preserving it. The research method is descriptive with qualitative explanations, and data collection techniques include interviews, observation, and documentation. Primary data was obtained directly from informants, and secondary data was analyzed from related documents. The Bone Regency cultural office has set a strategy for preserving cultural values and heritage by promoting cultural icons and increasing national recognition of intangible cultural heritage to revitalize cultural values among the people of Bone. Based on the results of data processing and analysis, it can be concluded that the cultural office's strategy for cultural conservation has been effective, although there are still areas for improvement in the future.